Management of Subtrochanteric Femoral Fracture Nonunions. Issue 6 (June 2020) - DeRogatis, Michael J.; Kanakamedala, Ajay C.; Egol, Kenneth A.
Abstract : Compared with other proximal femoral fractures, subtrochanteric fractures are at a higher risk for nonunion because of the high deforming forces in this region, the associated increased risk of malreduction, and the risk of poor bone healing secondary to bisphosphonate use frequently associated with these fractures. Further understanding of nonunion of subtrochanteric fractures is of increasing importance given the rise in incidence of subtrochanteric hip fractures. Surgeons should be aware of risk factors for nonunion and techniques for prevention as well as surgical management and complications associated with surgical implantation devices. Surgeons should also consider using adjuncts including bone-grafting and biologic agents.